Mathematical model of measuring details on a coordinate measuring machine - Bezvesilna, O.M. (Problems of Informatization and Management, 2025)
The paper explores the significance of measurement accuracy in coordinate measuring machines (CMM), highlighting their role in modern quality control processes. Key sources of measurement errors, including geometric, thermal, kinematic, and random factors, are analyzed. The study presents a novel approach for developing error correction algorithms aimed at enhancing measurement accuracy. The mathematical model developed considers the primary error sources and provides a structured framework for their correction. An algorithm for error correction is proposed, detailing the integration of systematic error adjustments into the measurement process. The algorithm is designed for real-time application, offering dynamic adaptability to varying operational conditions. The implementation of the proposed algorithm in CMM software demonstrates significant improvements in measurement precision. Results of modeling validate its effectiveness across diverse conditions. The paper concludes by emphasizing the scientific contribution of the proposed methodology, which combines theoretical advancements with practical applications to enhance the accuracy of CMM measurements.